Perception management and emotional commitment: lessons from post-earthquake schools - Akilli, Ceyda; Ozdemir, Tuncay Yavuz; Kaya, Vildan Donmus (Springernature, 2026)
Perception management practices within the dimensions of corporate image, reputation, and identity implemented by school administrators in schools defines leading the educators to act for shared goals and these implementations have positive effects on teachers in many areas, such as motivation, job satisfaction, and organizational citizenship. Emotional commitment is also among the organizational outcomes increased by perception management practices. This study examines the relationship between perception management practices implemented by school administrators, under corporate image, identity, and reputation dimensions, and teachers' emotional commitment in schools affected by the February 6 earthquakes in T & uuml;rkiye. In the study, Structural Equation Modeling (SEM) was used as the analytical method. The sample group was selected according to the stratified sampling method and 337 teachers from Elaz & imath;& gbreve;, Ad & imath;yaman, and Malatya were included. Data collection tools are Corporate Image Scale, Corporate Identity Scale, Corporate Reputation Scale and Emotional Commitment Scale. All scales demonstrated high internal consistency and satisfactory construct validity in confirmatory factor analyses. Model fit indices for the fully mediated SEM fell within acceptable ranges indicating that the measurement and structural components were well supported by the data. In the study, it was found that corporate identity positively influenced both corporate image and corporate reputation, and those two mediators each, in turn, significantly enhanced teachers' emotional commitment. Notably, the relationship between corporate identity and emotional commitment was fully mediated by corporate image and corporate reputation; highlighting that, in post-earthquake affected schools, identity messages only bolster commitment when they translate into observable corporate image and reputation building efforts.
Keywords: Perception management; Corporate identity; Corporate image; Corporate reputation; Emotional commitment; Post-earthquake